KOMUNIKASI KEBIJAKAN PUBLIK DALAM PENGELOLAAN PEDAGANG KAKI LIMA BERBASIS PADA KEARIFAN LOKAL (Kajian Pengelolaan Pedagang Kaki Lima di Kota Surakarta) - Nurati, Dian Esti (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
A study related to the policy of organization of Informal Traders in Surakarta which isbased on local wisdom, related to the condition in the field where Surakarta localgovernment in communicating the policy as the implementation of the minimumorganization of Informal Traders. Through observation and interview toward implementer,policy targets, and stake holders, such as Surakarta local legislative council, NGO, andInformal Traders observers. Based on the developmental phase of implantation model byGeorge Edward III, the communication process of policy communication in theorganization of Informal Traders in Surakarta consists of four factors: (1) Communication;(2) Resource; (3) Disposition and; (4) Bureaucracy. Implementation model by Grindle(1980) related to two aspects; policy contents and policy contexts, is considered havingminimal impact on its application. Based on the result of the analysis, this research provesthat policy communication helps people finding new norms and harmonization in thepolicy implementation. Policy communication also helps the implementer and the target ofpolicy to cooperate in achieving the purpose of policy. Local wisdom as the basis oforganizing and ordering Informal Traders based on socio-cultural approach, centered onthe nguwongke-uwong characteristic; where human are appreciated, respect each other,help each other to create togetherness and balance. Local wisdom always invests andrealizes communality, deliberation, dialog, and two way communication; therefore in theorganization of Informal Traders in Surakarta, harmony was realized through cultured Informal Traders organization.Keywords: Communication Public Policy, Organization of Informal Traders, LocalWisdom